Familial Crouzon syndrome - Samatha, Y. (Medknow Publications Pvt Ltd, 2010)
Crouzon syndrome is an autosomal dominant condition of the craniosynostotic syndromes without syndactyly and with various dentofacial anomalies. Craniosynostosis, maxillary hypoplasia, shallow orbits, ocular proptosis and hypertelorism are the characteristic features of Crouzon syndrome. This report describes the variable clinical features in affected individuals over two generations of a family with dentofacial deformities and review of literature.